THE SCHOLARLY LANDSCAPE OF FAZLUR RAHMAN’S DOUBLE MOVEMENT: A BIBLIOMETRIC ANALYSIS (1992–2025) - Billah Ali, Asyiq; Al-Adawiyah, Abidah; Alwan, Ariska (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2025)
The Double Movement approach developed by Fazlur Rahman has become one of the contemporary hermeneutical models that attempts to bridge the normative message of the Qur’an with the needs of modern society. This idea has been extensively researched in academic literature, both in terms of theory, application, and criticism. However, systematic mapping of research trends discussing the Double Movement is still rare. Through a descriptive quantitative approach and bibliometric analysis, as well as entering the keywords “Double movement AND Fazlur Rahman AND Hermeneutic,” this study analyzes the development of academic studies related to Fazlur Rahman’s Double Movement approach in the Google Scholar database during the period 1992 to 2025. A total of 159 valid publications were analyzed using Publish or Perish and VOSviewer to identify publication trends, citation patterns, author networks, and thematic structures. The results of this study show that there has been significant growth in publications over the last two decades, with the highest number of publications peaking in 2025 (37 publications), indicating sustained and increasing academic interest. This study contributes to providing an intellectual map of the development of Fazlur Rahman-s Double Movement studies, while also offering a foundation for further research in exploring the theoretical and practical analysis of this method. Therefore, the results of this study are expected to enrich contemporary interpretations and broaden methodological perspectives in Qur’anic studies.